Visual feedback training in young karate athletes - Vando, Stefano (CIC Edizioni Internazionali, 2014)
BACKGROUND: the purpose of this study was to examine the effect of a Visual Feedback Training (VFT) of the centre of pressure (COP) on postural sway in young karate athletes. METHODS: 38 young male karate athletes were recruited and randomly in 2 groups: experimental group (SG; n=19, age =16.54 ± 2.00 yrs) and the control group (CG; n= 19, age 16.45 ± 1.53 yrs). The SG performed a battery test of VFT on stabilometric platform screening in a monitor of COP in a real time. During 10-min of the test, athlete tries to bring his own body to the centre of COP. CG followed the same procedure of SG without receiving any feedback of their COP. RESULTS: ANOVA revealed an interaction training for type × F((1,360))=78.892 at p<0.001 (η(2)=33.178) and for training × time F((1,36))=7.479 with p<0.010 (η(2)=13.432). The results showed that VFT improved COP in SG of the 83% (p<0.0001) and decreased of the 26% in the CG (p<0.001). CONCLUSIONS: performing VFT improve stability and balance control and therefore greater ability to acquire motor control of the body in young karate athletes.